(untitled) (The Strategic Review for Southern Africa, 2020)
This article offers some historiographical reflections on independent Zimbabwe. While much has been written on the post-colonial period, some works were strongly informed by scholarly paradigms of the 1960s and 1970s, especially regarding the colonial legacy and inherited political structures, the land issue and the contentious and enduring debate on neocolonialism, although there were some post-modern shifts in the 1990s. Using some of the topical scholarship on the country, I trace the paradigmatic developments and narratives of the trajectory of the country’s political, economic and social record. While there is a deliberate focus on three broad aspects of ’nationalist’ history and its counternarratives, the historiography of the land as well as accounts of the crisis, I suggest that these have arguably constituted topical issues in scholarship. Although there are important areas on Zimbabwe’s academic landscape focusing on labour, gender, health, migration and environmental studies, among others warranting special attention, this article is restricted to insights on the areas identified. It is hoped that such bibliographical reflections can inform some interested students and scholars in sketching out some of the scholarship on Zimbabwe in the areas picked out.